CD8+ T-Cell Response to HIV Infection in the Era of Antiretroviral Therapy - Perdomo-Celis, Federico; Taborda, Natalia A.; Rugeles, Maria T. (Frontiers in Immunology, 2019)
Although the combined antiretroviral therapy (cART) has decreased the deaths associated with the immune deficiency acquired syndrome (AIDS), non-AIDS conditions have emerged as an important cause of morbidity and mortality in HIV-infected patients under suppressive cART. Since these conditions are associated with a persistent inflammatory and immune activation state, major efforts are currently made to improve the immune reconstitution. CD8+ T-cells are critical in the natural and cART-induced control of viral replication; however, CD8+ T-cells are highly affected by the persistent immune activation and exhaustion state driven by the increased antigenic and inflammatory burden during HIV infection, inducing phenotypic and functional alterations, and hampering their antiviral response. Several CD8+ T-cell subsets, such as interleukin-17-producing and follicular CXCR5+ CD8+ T-cells, could play a particular role during HIV infection by promoting the gut barrier integrity, and exerting viral control in lymphoid follicles, respectively. Here, we discuss the role of CD8+ T-cells and some of their subpopulations during HIV infection in the context of cART-induced viral suppression, focusing on current challenges and alternatives for reaching complete reconstitution of CD8+ T-cells antiviral function. We also address the potential usefulness of CD8+ T-cell features to identify patients who will reach immune reconstitution or have a higher risk for developing non-AIDS conditions. Finally, we examine the therapeutic potential of CD8+ T-cells for HIV cure strategies.